Adult Burkitt Lymphoma: An Unusual Presentation - Jiskani, Shahzad Ali; Zawar, Asfa; Naseem, Lubna (International Journal of Pathology, 2018)
Burkitt lymphoma is a disease of young population; especially children. It rarely occurs and presented in elderly group. World Health Organization (WHO) divided Burkitt lymphoma in endemic, sporadic and immunodeficiency – associated. The non–endemic variant occurs in children with abdominal involvement. We report a sporadic case presented at the age of 61 years old male with irregular thickening of parietal peritoneum and omentum without involving any lymph nodes.